Produtividade, qualidade do fruto e desenvolvimento radicular do abacaxizeiro irrigado por gotejamento - Silva, Elcides Rodrigues da [UNESP] (2014)
This research aimed to analyze productivity, root distribution, fruit quality and water use efficiency of the pineapple cv. Smooth Cayenne. The experiment was conduct at the Instituto Federal do Triângulo Mineiro, campus of Uberaba, city, MG state Brazil, consisting of five irrigation (25, 50, 75, 100 and 125% of crop evapotranspiration) and two positions of drips: surface and subsurface (10 cm depth). It was use the trench method for quantification of the root system by digital images with the SAFIRA® 1.1 software. It was evaluated the following parameters: average fruit weight with and without crown (AFWWC, AFWOC), average fruit, stalk and stem diameter (AFD, AAD and AED), fruit resistance with and without shell (FRWC, FROC), juice yield (JY), total soluble solids (TSS), pH, total titratable acidity (TTA), ratio (TSS / TTA) and water use efficiency (WUE). The surface drip irrigated productivity features 6.13 t ha-1 higher than the subsurface drip and promotes area and root length with 53 and 54% higher than the subsurface, respectively. As to the roots depth showed larger area and length at the 0 to 10 cm layer, with values 49 and 52% higher than those obtained in the 10 to 20 cm layer. As to the average fruit weight with and without crown, there is no significant difference between irrigation depths applied, however, the surface drip line irrigation showed significant difference obtained with average fruit weight higher than the subsurface drip. The depth and the position of the drip line don’t influenced AFD, AAD, AED, FRWC, FROC, JY, TSS, pH, TTA, SST / ATT. The depth replacement of 25% of crop evapotranspiration provided greater efficiency of water use for pineapple production